滚珠丝杠副 (2025)
本发明公开了一种滚珠丝杠副，包括丝杠轴、丝杠螺母、滚珠和滚珠反向器，丝杠轴和丝杠螺母的螺旋齿在轴向上以交叉方式配置，从而在螺旋齿两侧分别形成一个螺旋通道，这两个螺旋通道既是滚珠的负荷行进通道，也是其无负荷返回通道；在丝杠轴和丝杠螺母螺旋齿的两个侧面上均有螺旋形沟道作为滚珠的螺旋运动滚道面，在螺旋通道中滚珠与滚道面的接触角α大于45°；在丝杠螺母螺旋齿的两端处各有一个滚珠反向器，使滚珠能够从丝杠螺母螺旋齿的任意一侧运动至另一侧，从而形成完整的滚珠循环通道；当滚珠丝杠副具备两个或多个滚珠循环通道时，丝杠螺母螺旋齿被分成两段或多段，每段螺旋齿与其两端的反向器都可以形成一个完整的滚珠循环通道。 The invention discloses a ball screw pair. The ball screw pair comprises a screw shaft, a screw nut, a ball and ball reversers; spiral teeth of the screw shaft and the screw nut are arranged in a crossed manner in the axial direction, the two sides of the spiral teeth each form a spiral channel, the two spiral channels are ball load advancing channels and also non-load returning channels, spiral trenches are arranged on two side faces of the spiral teeth of the screw shaft and the screw nut and serve as the spiral motion rolling path faces of the ball, in the spiral channels, the contact anglealpha of the ball and the rolling path faces is larger than 45 degrees, two ends of the spiral teeth of the screw nut are each